Performance of Transgenic Chrysanthemum Harbouring Wasabi Defensin Gene for White Rust Disease Resistance (HAYATI Journal of Biosciences, 2022)
This study was intended to obtain white rust (Puccinia horiana) disease resistance Chrysanthemum transformed with wasabi defensin gene through mediation of Agrobacterium tumefaciens from three explant sources, i.e., leaf, lateral shoot bud, and internode. Observations were made on transformation efficiency, PCR analysis, in vitro and ex vitro disease resistance tests. Results showed that efficiency of transgenic callus and shoot regeneration was found both highest from lateral shoot buds (57.5% and 50.0%, respectively). PCR analysis showed that three putative transgenic plantlets from lateral shoot buds and one from leaf explant were putative transgenic carrying the wasabi, hpt, and nptII genes. Rooting test showed that the highest number of rooted plants was found in treatment of hygromycin (Hg) 25 mg L-1 (81%) and lowest was in treatment combination of kanamycin (Km) 50 mg L-1 + Hg 25 mg L-1 (25%). In vitro disease resistance test with sorus inoculation of P. horiana, directly on the leaves, resulted in 20 resistant plants out of 30 putative transgenic plants (66.67%). Ex vitro testing on adult plants of the same samples in a confined closed greenhouse (CGH) resulted in average of 80% transgenic Chrysanthemum plants were resistant, whereas in control plants caused white rust disease symptom.